Pengaruh Ketinggian Permukaan Air Terhadap Kinerja Prototype Oscillating Water Column - Sa'dullah, Moch. Sa'dulloh; Djoko Wahyudi; Muhammad Fathuddin Noor (STTI Bontang, 2023)
Indonesia is a country that has a vast ocean or water area. This makes Indonesia very potential for developing electricity generation using ocean wave energy. The potential and kinetic energy in ocean waves can be a great opportunity to convert it into electrical energy. There are several ways to utilize ocean wave energy, one of which is by using an Oscillating Water Column Ocean Wave Power Plant (PLTGL-OWC). In general, the performance of PLTGL OWC depends on the characteristics of the water waves entering the OWC oscillating column. Therefore, the aim of this research is to determine the influence of the characteristics of the water waves produced on the performance of the PLTGL OWC prototype using experimental methods and varying water surface heights of 20 cm, 25cm and 30cm. From the results of the research that has been carried out, the prototype performance obtained at each water level has an OWC column efficiency value of 0.072%, 0.063% and 0.022%. Meanwhile, the largest voltage and current produced by the PLTGL OWC prototype was 5.4 Volts and 13.53 mA.